Mali : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2004)
The report reviews the basic data, and selected social and demographic indicators of Mali. It also analyzes the revised methodology for national accounts. It provides the details of the IMF's projections and estimates of Mali's gross domestic product at constant 1987 prices, in previous and new methodologies. It also compares origin and use of resources, implementation of the public investment program, 1996-2002, agricultural production and average producer prices 1996/97-2002/03, production and cost of cotton fiber, government expenditure, revenue performance, functional classification of budgetary expenditures during 1996-2002, claims on the government, 1996-October 2003, tax summary, and so on.